Diseases In The Aquarium Fishes: Challenges And Areas Of Concern: An Overview - Rao, M Vishwas; Kumar, TT Ajith; Haq, MA Badhul (International Journal of Environment, 2013)
Progress over the past years has revealed much strength of the ornamental fish as an alternative model for the environmental sideline in the aquaculture both in fresh water and marine waters. These include low rearing costs, an earlier life stage. Aquarium fish are one of the largest groups of pets in the world. There is an increasing demand for the veterinary services that are related to the ornamental fish. Early clinical signs in many infectious and noninfectious diseases of fish are manifested by the skin. More diseases in fish have been described and have been associated with the research for the future has been discussed. This article also describes the more common environmental and pathogen related dermatologic diseases of the aquarium fishes. Disease prevention, control and various treatment methods also have been discussed. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 127-146 DOI: http://dx.doi.org/10.3126/ije.v2i1.9216